Review of the research program of the Partnership for a New Generation of Vehicles : fifth report (National Academy Press, 1999)
This fifth review of the Partnership for a New Generation of Vehicles assesses progress made in the program towards the development of high fuel economy vehicles. One of the goals of the program is to develop midsize sedans with up to three times the fuel economy of today's vehicles. Concept vehicles are slated for 2000 and production prototypes for 2004. The book addresses engine technologies, batteries for energy storage, fuel cells, lightweight materials, fuels, emissions control systems, power electronics, and vehicle systems engineering.
Keywords: Partnership for a New Generation of Vehicles (U.S.); Automobiles -- Energy consumption -- Research -- United States.; Automobile industry and trade -- Government policy -- United States.; Automobiles -- Industrie et commerce -- Politique gouvernementale -- États-Unis.; TECHNOLOGY & ENGINEERING -- Power Resources -- General.; BUSINESS & ECONOMICS -- Industries -- Energy.; SCIENCE -- Energy.; Automobile industry and trade -- Government policy; United States; Samfundsvidenskab -- Økonomi.